Trophic relationship between the invasive parasitic copepod Mytilicola orientalis and its native blue mussel (Mytilus edulis) host - Goedknegt, Anouk; Shoesmith, D. David; Jung, Alexa Sarina; Luttikhuizen, Pieternella; Philippart, C. J. M. Katja; van der Veer, H.W. Henk; Thieltges, D.W. David (NIOZ Royal Netherlands Institute for Sea Research, 2017)
Research objective: Invasive parasites can spill over to new hosts in invaded ecosystems with often unpredictable trophic relationships in the newly arising parasite-host interactions. In European seas, the intestinal copepod Mytilicola orientalis was co-introduced with Pacific oysters (Magallana gigas) and spilled over to native blue mussels (Mytilus edulis), with negative impacts on the condition of infected mussels. However, whether the parasite feeds on host tissue and/or stomach contents is yet unknown. To answer this question, we performed a stable isotope analysis in which we included mussel host tissue and the primary food sources of the mussels, microphytobenthos (MPB) and particulate organic matter (POM). Type of research, method & collection of data: Stable isotope analysis of four different types of samples 1) parasite Mytilicola orientalis, 2) host Mytilus edulis, 3) particulate organic matter (POM) and 4) microphytobenthos (MPB).